From Bleeding Control to Health: Implementing Multidimensional and Multidisciplinary Hemophilia Care Into the Era of Therapeutic Innovation - Nicolas Giraud; Yesim Dargaud (Haemophilia, 2026)
ABSTRACT Introduction Over the past decade, hemophilia management has been transformed by modern prophylactic strategies, achieving dramatic reductions in annualized bleeding rates (ABR), often approaching zero. However, the conceptual evolution of hemophilia care toward multidimensional health assessment and comprehensive multidisciplinary management was initiated more than two decades ago through the adoption of functional, patient‐reported, and biopsychosocial outcome frameworks. Despite these advances, their implementation in routine clinical practice remains incomplete, highlighting a persistent disconnect between hemostatic control and overall health. Aim To examine how recent therapeutic innovations should be integrated within established multidimensional models of hemophilia care and to identify the remaining barriers to their implementation. Methods Narrative literature review combined with the joint perspective of a French patient representative and hematologist. Results We discuss the need to operationalize multidimensional outcome assessment by integrating patient‐reported outcomes, joint health, functional status, participation, and sex‐specific bleeding phenotypes, including menstrual bleeding and limitations of ABR as a measure of treatment success. Therapeutic innovation also introduces new challenges requiring individualized care, behavioral adaptation, long‐term safety surveillance, and shared decision‐making. Persistent implementation gaps include fragmented care pathways, unequal access to multidisciplinary expertise and specialized laboratory support, and limited integration of psychological, functional, cardiovascular, and behavioral dimensions into routine care. Conclusions The challenge for modern hemophilia care is no longer to redefine comprehensive, patient‐centered management, but to translate long‐established multidimensional frameworks into everyday clinical practice. Achieving sustained health, autonomy, and meaningful participation will require strengthening multidisciplinary care models, and ensuring equitable implementation of comprehensive care.